1999
DOI: 10.1016/s0735-1097(98)00550-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of microtubules in the contractile dysfunction of hypertrophied myocardium

Abstract: Excess microtubule density, therefore, is equally important to both cellular and to myocardial contractile dysfunction caused by chronic, severe pressure-overload cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 14 publications
4
46
0
1
Order By: Relevance
“…In this work, we have found that microtubule depolymerization increases neither resting nor peak activated Ca 2ϩ levels in normal or hypertrophied cardiocytes (30), and colchicine increases neither cAMP levels, peak activated Ca 2ϩ levels, nor the rate of rise or fall of intracellular Ca 2ϩ in normal or hypertrophied myocardium (32). Nevertheless, it has been suggested that colchicine increases Ca 2ϩ current density and the intracellular Ca 2ϩ transient in adult cardiocytes (13) via ␣,␤-tubulin heterodimers acting as a functional analog of G proteins to activate adenyl cyclase when the free tubulin concentration is increased by microtubule depolymerization.…”
Section: Is There a Specific Link Between Microtubule Network Densitymentioning
confidence: 64%
“…In this work, we have found that microtubule depolymerization increases neither resting nor peak activated Ca 2ϩ levels in normal or hypertrophied cardiocytes (30), and colchicine increases neither cAMP levels, peak activated Ca 2ϩ levels, nor the rate of rise or fall of intracellular Ca 2ϩ in normal or hypertrophied myocardium (32). Nevertheless, it has been suggested that colchicine increases Ca 2ϩ current density and the intracellular Ca 2ϩ transient in adult cardiocytes (13) via ␣,␤-tubulin heterodimers acting as a functional analog of G proteins to activate adenyl cyclase when the free tubulin concentration is increased by microtubule depolymerization.…”
Section: Is There a Specific Link Between Microtubule Network Densitymentioning
confidence: 64%
“…A computer-controlled servo motor system was used to mechanically test the papillary muscles. Data examining the effect of POH and treatment with colchicine on myocardial contractile function from these same papillary muscles have been previously published (52). The current study examined the effect of POH and treatment with colchicine on myocardial constitutive viscoelastic properties.…”
Section: Methodsmentioning
confidence: 96%
“…RV POH was induced by partially occluding the pulmonary artery with a 2.9-mm inner diameter band using previously described methods (52). Briefly, adult cats weighing 2.6-3.9 kg were first anesthetized with ketamine hydrochloride (15 mg/kg im), meperidine (2.2 mg/kg im), and acepromazine maleate (0.25 mg/kg im), intubated, and then placed on a respirator.…”
Section: Pulmonary Artery Bandingmentioning
confidence: 99%
See 2 more Smart Citations